Effectiveness of intubation devices in patients with cervical spine immobilisation: a systematic review and network meta-analysis - Singleton, Barry N.; Morris, Fiachra K.; Yet, Barbaros; Buggy, Donal J.; Perkins, Zane B. (British journal of anaesthesia : BJA, 2021)
Cervical spine immobilisation increases the difficulty of tracheal intubation. Many intubation devices have been evaluated in this setting, but their relative performance remains uncertain. MEDLINE, EMBASE, and the Cochrane Library were searched to identify randomised trials comparing two or more intubation devices in adults with cervical spine immobilisation. After critical appraisal, a random-effects network meta-analysis was used to pool and compare device performance. The primary outcome was the probability of first-attempt intubation success (first-pass success). For relative performance, the Macintosh direct laryngoscopy blade was chosen as the reference device. We included 80 trials (8039 subjects) comparing 26 devices. Compared with the Macintosh, McGrath™ (odds ratio [OR]=11.5; 95% credible interval [CrI] 3.19–46.20), C-MAC D Blade™ (OR=7.44; 95% CrI, 1.06–52.50), Airtraq™ (OR=5.43; 95% CrI, 2.15–14.2), King Vision™ (OR=4.54; 95% CrI, 1.28–16.30), and C-MAC™ (OR=4.20; 95% CrI=1.28–15.10) had a greater probability of first-pass success. This was also true for the GlideScope™ when a tube guide was used (OR=3.54; 95% CrI, 1.05–12.50). Only the Airway Scope™ had a better probability of first-pass success compared with the Macintosh when manual-in-line stabilisation (MILS) was used as the immobilisation technique (OR=7.98; 95% CrI, 1.06–73.00). For intubation performed with cervical immobilisation, seven devices had a better probability of first-pass success compared with the Macintosh. However, more studies using MILS (rather than a cervical collar or other alternative) are needed, which more accurately represent clinical practice. PROSPERO 2019 CRD42019158067 (https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=158067).